2006
DOI: 10.1152/physiolgenomics.00293.2005
|View full text |Cite
|
Sign up to set email alerts
|

Altered metabolic responses to intermittent hypoxia in mice with partial deficiency of hypoxia-inducible factor-1α

Abstract: We have previously shown that exposure of C57BL/6J mice to intermittent hypoxia (IH) leads to 1) hypertriglyceridemia due to upregulation of pathways of lipid biosynthesis, including sterol regulatory element binding protein (SREBP)-1 and stearoyl CoA desaturase (SCD)-1; and 2) hypercholesterolemia due to impaired cholesterol uptake. The goal of the present study was to examine whether hypoxia-inducible factor (HIF)-1 is implicated in changes in lipid metabolism induced by IH. Lean HIF-1alpha (Hif1a)(+/-) mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
120
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 153 publications
(127 citation statements)
references
References 66 publications
4
120
3
Order By: Relevance
“…CIH doubled circulating levels of leptin, which was consistent with our previous observations in short-term IH. 11,13,24 Serum corticosterone levels were identical in both groups ( Table 1), suggesting that mice exposed to CIH did not exhibit evidence of stress. CIH resulted in an increase in fasting serum total cholesterol and triglyceride levels ( Table 2), which was similar to our previous observations.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…CIH doubled circulating levels of leptin, which was consistent with our previous observations in short-term IH. 11,13,24 Serum corticosterone levels were identical in both groups ( Table 1), suggesting that mice exposed to CIH did not exhibit evidence of stress. CIH resulted in an increase in fasting serum total cholesterol and triglyceride levels ( Table 2), which was similar to our previous observations.…”
Section: Resultsmentioning
confidence: 89%
“…CIH resulted in an increase in fasting serum total cholesterol and triglyceride levels ( Table 2), which was similar to our previous observations. 13,24 Liver cholesterol content was significantly depleted during the exposure, whereas liver triglyceride, phospholipid, and FFA content remained unchanged (Table 2), revealing a marked difference with ob/ob mice, which had significant increases in liver triglyceride and phospholipid content after 12 weeks' exposure to CIH. 12 Liver injury in CIH was assessed by measuring of the levels of key liver enzymes in the serum.…”
Section: Resultsmentioning
confidence: 98%
“…A variety of studies based on animal models indicate that hypoxia can alter glucose homeostasis (Cheng et al, 1997;Li et al, 2006). Polotsky described that long-term exposure to intermittent hypoxia increased levels of insulin and glucose intolerance in obese, leptindeficient mice (Polotsky et al, 2003).…”
Section: Osas and Insulin Resistancementioning
confidence: 99%
“…Through this mechanism, hypoxia in mammals could promote persistent hypertriglyceridemia. In support, this same group of researchers previously found that mice with transgenic partial deficiency in hypoxia-inducible factor-1␣ (HIF-1␣ϩ/Ϫ) showed smaller increases in SREBP and SCD-1 and proportionately smaller increases in serum lipids in response to intermittent hypoxia (7). Future studies are needed to determine whether the hypertriglyceridemia is of benefit in mammals and whether this benefit outweighs the adverse health consequences of 15-20% increase in serum triglycerides.…”
mentioning
confidence: 90%
“…In the fission yeast, Saccharomyces pombe, severe hypoxia activates SRE-1, and this in turn upregulates genes for low oxygen sterol synthesis and genes promoting the switch from aerobic to anaerobic survival and growth, genes essential for adapting to hypoxia and allowing sterol synthesis even during hypoxia. This system, at least in fission yeast, can override the sterol negative feedback, such that it is possible under conditions of hypoxia to have persistently higher levels of specific lipids, necessary for maintaining membrane stability and fluidity (7).…”
mentioning
confidence: 99%